Nutritional knowledge, fiber intake, body mass index, and sex associated with constipation symptoms in Peruvian adults - Pablo C. Rojas-Rojales; David Javier-Aliaga; Yaquelin E. Calizaya-Milla; Jacksaint Saintila (Scientific Reports)
Abstract Functional constipation is a common gastrointestinal disorder influenced by dietary, anthropometric, and demographic factors. However, the combined impact of these factors on constipation symptoms remains underexplored, particularly within the Peruvian population. To assess the association of nutritional knowledge, fiber-rich food consumption, body mass index (BMI), and sex with functional constipation symptoms in Peruvian adults. A cross-sectional study was conducted among 404 Peruvian adults selected through non-probability sampling. Nutritional knowledge (assessed using the Dietary Fiber Habits and Knowledge Questionnaire), fiber-rich food consumption (measured with the Block Instrument), BMI (self-reported and calculated), and constipation symptoms (evaluated using the Rome III International Diagnostic Questionnaire) were analyzed. Hierarchical regression analysis was performed to evaluate the impact of the variables on constipation symptoms. The hierarchical regression analysis, conducted in four blocks, demonstrated a progressive increase in the explained variance. In the fourth block, nutritional knowledge (β = − 0.173, p = 0.006, CI [− 0.296, − 0.050]) and consumption of high-fiber foods (β = − 0.227, p < 0.001, CI [− 0.351, − 0.103]) were associated with a reduction in constipation symptoms, while BMI (β = 0.230, p < 0.001, CI [0.108, 0.353]) and being female (β = 0.153, p = 0.014, CI [0.031, 0.274]) were associated with an increase in symptoms. The final model accounted for 16.4% of the total variance (adjusted R2 = 0.164), with fiber consumption contributing to a 5.2% increase in explained variance (∆R2 = 0.052). These findings underscore the importance of implementing public health educational and dietary strategies to address constipation through preventive and personalized approaches.